Okay, so first we need to work out the gradient, m.
To do this use the formula change in y/ change in x
So If we pick two points, say 0,-3 and -4,-5 the change in y is from -3 to -5 so it is -2 and the change in x is from 0 to -4 so is taking away 4 so the gradient is -2/-4 which is 1/2.
Then we need to work out the y intercept, c.
Substitute the gradient into y= Mx+ c to get y = 1/2 x + c. Use a point to substitute in and solve:
Eg 4, -1 —> -1 = 1/2 x 4 + c
Then -1 = 2 + c
Then -3 = c
So you get the end equation of
Y = 1/2x -3
Let me know if you have any questions